Primary structure and expression of a functional human glucocorticoid receptor cDNA - Hollenberg, Stanley M. (Nature, 1985)
Identification of complementary DNAs encoding the human glucocorticoid receptor predicts two protein forms, of 777 (α) and 742 (β) amino acids, which differ at their carboxy termini. The protein s contain a cysteine/lysine/arginine-rich region which may define the DNA -binding domain. Pure radiolabelled glucocorticoid receptor, synthesized in vitro, is immunoreactive and possesses intrinsic steroid-binding activity characteristic of the native glucocorticoid receptor.